ANALISIS DIVERSIFIKASI REKSADANA SAHAM DN REKSADANA PENDAPATAN TETAP - , Dewi Masyithoh Khairani Lubis ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study is an empirical study to analyze equity fund performance compared to fixed income fund performance. The performance seen from the ability to diversify the risk and measured by using Reward to Diversification (RDIV) variable. The sample was selected by purposive sampling method with filtering active mutual fund from 2006 to June 8 th , 2011. Than selected only equity fund and fixed income fund. The analysis show that there are significant differences of the equity fund performance and fixed income fund performance. Equity fund performance only better than fixed income fund performance when the economy is stable. Equity fund performance is not only better from the excess return side, but also from the diversification side. However, when the economic crisis happens, such as in 2008 and 2011, equity fund performance was worse than fixed income fund performance. When the economic crisis happens, equity fund performance will fall very sharply, so it is lower than the performance of fixed income fund. This is because of the stability of fixed income fund return than equity fund return.